PENGARUH PROMO SHOPEEFOOD TERHADAP MINAT BELI PENGGUNA SHOPEE (Di Daerah Tangerang Selatan) - Izella Vania; Remista Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This research aims to describe and analyze the effect of ShopeeFood promos on the buying interest of Shopee application users in South Tangerang area. This study uses a questionnaire via google form as a research instrument. The data was processed using SPSS v25 software using coefficient of correlation test, namely the t test, the coefficient of determination, and simple linear regression. The correlation coefficient test r count of 0.734 which means that the buying interest has a strong relationship with ShopeeFood promos. The t test results showed that ShopeeFood promo has a significant effect on consumer buying interest as evidenced by the value of t count 10.800 > t table 1,98373 and the ShopeeFood promo variable showed by determination test of 53.8% which means it has a positive effect on the level of consumer buying desire while the rest influenced by other factors outside this research. The simple linear regression showed Y= -5,940 + 1.016X as the formula, which means that if the promo has no buying interest, the consumer is in a condition of -5,940 and if the promo increases by 1 unit, the buying interest increases by 1,016 units. It can be seen that the promo is very influential on consumer buying interest.